2006
DOI: 10.1021/jp0560213
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of Phenol:  A Mechanistic View

Abstract: The current work utilizes the ab initio density functional theory (DFT) to develop a molecular level of the mechanistic understanding on the phenol alkylation in the presence of a cation-exchange resin catalyst, Amberlyst-15. The catalyst is modeled with the benzene sulfonic acid, and the effect of this acid on olefins such as isopropene (i-Pr) and tributene (t-Bu) in a phenol solution mimics the experimental condition. A neutral-pathway mechanism is established to account for early-stage high concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 75 publications
2
28
0
Order By: Relevance
“…The alkylation of m-cresol with t-butanol were evaluated and the authors suggested that the strong acidic sites present in the catalysts are responsible for the C-alkylation. 13 A systematical theoretical study using ab initio calculation 21 and ab initio density functional theory (DFT) 12 were reported in the literature. They concluded that O-alkylation to form the phenolic ether is the product most energetically favorable in neutral conditions and an ionic rearrangement mechanism describes intramolecular migrations of the alkyl group from the phenolic ether to form C-alkylphenols.The intermediate from the C-alkylation is more stable and as a result, the O-alkylated products disappear gradually.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The alkylation of m-cresol with t-butanol were evaluated and the authors suggested that the strong acidic sites present in the catalysts are responsible for the C-alkylation. 13 A systematical theoretical study using ab initio calculation 21 and ab initio density functional theory (DFT) 12 were reported in the literature. They concluded that O-alkylation to form the phenolic ether is the product most energetically favorable in neutral conditions and an ionic rearrangement mechanism describes intramolecular migrations of the alkyl group from the phenolic ether to form C-alkylphenols.The intermediate from the C-alkylation is more stable and as a result, the O-alkylated products disappear gradually.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that O-alkylation to form the phenolic ether is the product most energetically favorable in neutral conditions and an ionic rearrangement mechanism describes intramolecular migrations of the alkyl group from the phenolic ether to form C-alkylphenols.The intermediate from the C-alkylation is more stable and as a result, the O-alkylated products disappear gradually. 12,21 The liquid phase alkylation of phenol with 1-octen-3-ol over niobium phosphate an ionic rearrangement of the O-alkylated products to C-alkylated products can occur. A mechanistic study are in progress in our laboratory to clarify this point.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanistic aspect of the electrophilic attack to the phenol is investigated from a theoretical point of view by Tang and coworkers. These authors suggested that the addition of the sulfonic acid to the olefins occurs leading to the formation of a sulfonic ester intermediate, which, in turns, reacts with phenol to form the products of alkylation [31].…”
Section: Introductionmentioning
confidence: 99%
“…These authors suggested that an olefin reacts with a sulfonic acid leading to the formation of a sulfonic ester intermediate, which, in turns, reacts with phenol to form the products of alkylation [25].…”
Section: Introductionmentioning
confidence: 99%